"Gli alberi" e Lu Xun, «una nuova razionalità». On the commentary of "Questo Muro" by Franco Fortini (inOpera Esercizi di lettura su testi contemporanei, 2024)
Shortly after the publication of Questo muro, in a letter dated June 7, 1973, Italo Calvino comments on Fortini’s collection, focusing on the particular use of "natural and high-lyrical images". Following Calvino’s analysis of the meaning of vegetal figurae, a commentary on one of the poems from Questo muro is offered as an example.
Keywords: Franco Fortini; Questo Muro; Contemporary Italian Literature; Gli alberi; Lu Xun